Understanding the Fundamental Basis for Biofilm Formation on Plastic Surfaces: Role of Conditioning Films - Bhagwat, Geetika; O’Connor, Wayne; Grainge, Ian; Palanisami, Thava (Frontiers in Microbiology, 2021)
Conditioning films (CFs) are surface coatings formed by the adsorption of biomolecules from the surrounding environment that can modify the material-specific surface properties and precedes the attachment of microorganisms. Hence, CFs are a biologically relevant identity that could govern the behaviour and fate of microplastics in the aquatic environment. In the present study, polyethylene terephthalate (PET) and polylactic acid (PLA) plastic cards were immersed in natural seawater to allow the formation of CFs. The changes in the surface roughness after 24 hrs were investigated by atomic force microscopy (AFM) and the surface changes were visualised by scanning electron microscopy (SEM). The global elemental composition of the conditioned surface was investigated by energy dispersive spectroscopy (EDS). Results indicated that marine conditioning of PET and PLA samples for 24 hrs resulted in an increase of approximately 11% and 31% in the average surface roughness respectively. SEM images revealed the attachment of coccoid-shaped bacterial cells on the conditioned surfaces and the accumulation of salts of sodium and phosphate-containing precipitates was revealed through the EDS analysis. The results indicate that the increase in surface roughness due to conditioning is linked to a material’s hydrophilicity leading to a rapid attachment of bacteria on the surfaces. Further investigations into the conditioning films can unfold crucial knowledge surrounding the plastic-microbe interaction that has implications for medical, industrial, and environmental research.